2023
DOI: 10.3389/fonc.2023.1097911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of fruquintinib and regorafenib in the treatment of metastatic colorectal cancer: A real-world study

Abstract: BackgroundFruquintinib and regorafenib have been approved for the third-line therapy of metastatic colorectal cancer (mCRC) in China. However, at present, there is a lack of head-to-head clinical trials on the comparison of efficacy and safety between the two drugs.Materials and methodsThe data of patients with mCRC who were treated with fruquintinib or regorafenib after the standard chemotherapy in Zhejiang Provincial People’s Hospital from October 2018 to November 2021 were collected and analyzed. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The results of Deng et al [ 31 ] suggested that FP had a better PFS (5.9 vs 3.0 months, P = 0.009) and OS (17.5 vs 11.3 months, P = 0.008) than F in the treatment of mCRC. FP also had a longer PFS (5.9 vs 3.8 months, P = 0.018) and OS (17.5 vs 14.8 months, P = 0.044) than RP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Deng et al [ 31 ] suggested that FP had a better PFS (5.9 vs 3.0 months, P = 0.009) and OS (17.5 vs 11.3 months, P = 0.008) than F in the treatment of mCRC. FP also had a longer PFS (5.9 vs 3.8 months, P = 0.018) and OS (17.5 vs 14.8 months, P = 0.044) than RP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Deng et al [ 31 ] found that although there was no significant difference in median PFS between RP and R (3.8 vs 2.4 months, P = 0.262), RP had a longer OS than R (14.8 vs 10.0 months, P = 0.045), which was inconsistent with our findings [median OS (RP: 14.1 months, R: 15.7 months, P = 0.08)]. In a real-world study, Jiang et al [ 32 ] also reported that RP did not prolong the median OS compared with R alone (11.0 vs 11.2 months, P = 0.814).…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, many patients might progress of the first-line therapy and switch to other combined chemotherapy regimens as second-line treatment, achieving survival benefits consecutively. 8 Still and all, a certain amount of patients were able to receive the third-line treatment; to our knowledge, the FRESCO and CONCUR trials convinced that the antiangiogenic small-molecule tyrosine kinase blockades (TKIs) fruquintinib and regorafenib might further bring survival benefits for patients with CRC and were approved by guidelines as the third-line treatment for patients with metastatic CRC in China, respectively. 9 , 10 However, the disappointing ORR of fruquintinib and regorafenib (4.7% and 4.0%, respectively) highlighted that novel therapeutic options were still needed to be explored to provide patients with promising efficacy and acceptable safety profile in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The Vascular Endothelial Growth Factor 2 is a receptor of tyrosine kinases that have been implicated in tumor angiogenesis, a key feature of many cancers 48 . However, the number of drugs for cancer treatments targeting Vegfr2 are limited 49 . Sorafenib is the main reference ligand as an oral multi-target kinase inhibitor of tumor genesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%